Паэз!я Наталл! Арсенневай ваеннага часу - Nikitiuk-Perkowska, Wioleta (Acta Polono-Ruthenica, 2018)
The wartime poetry of Belarussian emigre poet Natalia Arsienniewa has a significant place not only in her literaly output, but also in the whole Belarussian literature. This type of work is the least explored in artistic biography of the poet. During the war, Natalia Arsienniewa departs from poetising nature typical for the pre-war period. At that time she focuses all her attention on the description of war surrounding the tragic realities of everyday life. Then in her poems dominate so-called: poems-calls to compatriots, poems-apostrophes to Homeland, as well as reflections about human existence, including the fate of the poet. A kind of poetic summary of this period is a collection of poems Siahonnia, released in 1944 in Minsk.